Semiotic Analysis of Pegon Arabic T-Shirt: Alternative Dakwah for Millennials in Caring for the Nusantara Islamic Heritage - Yunianta, Rohmat Dwi; Aini, Nur (JASNA : Journal For Aswaja Studies, 2024)
This research on the Arabic Pegon t-shirt was qualitative research based on Charles S. Pierce's semiotic theory, which revealed the existence of icons, indexes and symbols in every text and visual communication. Therefore, this research attempted to uncover the iconization, indexicality and symbolization contained in t-shirt designs that used Pegon Arabic script and find the meaning behind the use of these three aspects of language signs. This research data came from Arab Pegon t-shirts produced and marketed by a millennial at the â€œGaleri Sahayaâ€ Pati outlet. This research concluded that the use of Pegon Arabic script on t-shirts was a representation of Indonesian cultural symbols, which were outlined in several t-shirt design themes, namely the themes of mahabbah (love), hubbul wathon (love of the homeland), syauq (longing), and adab (manners). The themes raised in the Arabic Pegon t-shirts were general (universal) themes that could be accepted by all groups and groups with the aim that the Arabic Pegon script could be known externally by all levels of society and revive the enthusiasm to care for the Islamic heritage of the archipelago.